Vaccine efficacy against SARS-CoV-2 for Pfizer BioNTech, Moderna, and AstraZeneca vaccines: a systematic review - Reynolds, Lia; Dewey, Cate; Asfour, Ghaid; Little, Matthew (Frontiers in Public Health, 2023)
The purpose of this systematic review was to report on the vaccine efficacy (VE) of three SARS-CoV-2 vaccines approved by Health Canada; Pfizer BioN-Tech, Moderna, and AstraZeneca. Four databases were searched for primary publications on population level VE. Ninety-two publications matched the inclusion criteria, and the extracted data was separated by vaccine type: mRNA vaccines (Pfizer and Moderna) and the AstraZeneca vaccine. The median VE for PCR test-positive and various levels of clinical disease was determined for the first and second doses of both vaccine types against multiple SARS-CoV-2 variants. The median VE for PCR test-positive infections against unidentified variants from an mRNA vaccine was 64.5% and 89% respectively after one or two doses. The median VE for PCR test-positive infections against unidentified variants from the AstraZeneca vaccine was 53.4% and 69.6% respectively after one or two doses. The median VE for two doses of mRNA for asymptomatic, symptomatic, and severe infection against unidentified variants were 85.5%, 93.2% and 92.2% respectively. The median VE for two doses of AstraZeneca for asymptomatic, symptomatic, and severe infection against unidentified variants were 69.7%, 71% and 90.2% respectively. Vaccine efficacy numerically increased from the first to second dose and increased from the first two weeks to the second two weeks post vaccination for both doses but decreased after four months from the second dose. Vaccine efficacy did not differ by persons’ age.